Damage by Acanthoscelides clitellarius (Coleoptera: Bruchidae), Lepidoptera (Pyralidae) and Diptera in seeds of Piptadenia communis (Leguminosae) - Santos, Germi; Zanuncio, Teresinha; Assis Junior, Sebastiăo; Zanuncio, José (Bosque (Valdivia), 1998)
Fruits collected from Piptadenia communis (Leguminosae) trees in Viçosa, Minas Gerais, Brazil, were found to be damaged by five species of insects, Acanthoscelides clitellarius (Coleoptera; Bruchidae) being the most destructive. Damage caused by this insect and by two unidentified Lepidoptera and two Diptera species were 34.84±2.34, 5.64±0.98 and 1.46±0.21%. Consumption for the development of an individual of each of the species was 3.40, 16.57 and 20.50 mg repectively. Each bruchid larva uses only one P. communis seed, apparently optimizing with this, their source of food.